DUKUNGAN SOSIAL KELUARGA TERHADAP RESILIENSI PADA IBU DENGAN ANAK RETARDASI MENTAL - Karina Safitri; Iriani Indri Hapsari (Journal of Research and Measurement in Psychology, 2013)
Abstract The study was conducted to determine the effect of family social support against the reciliency of mother with mentally retarded children. The population in this study were all mothers who have mentally retarded child at South Jakarta. Samples used in this study amounted to 56 mothers who have mentally retarded children. Sampling using a purposive sampling technique. The study using quantitative methods with two instruments as a measure of family sosial support and reciliency measurement tools from the RQ-Test made by Reivich and Shattle (2002) that has been modified. Processing method of data analysis techniques in the testing hypothesis using Regression Analysis. The hypothesis in this study is that there is significant influence between family social support and reciliency of mother with mentally retarded children. Result explains that there is significant influence between family social support against reciliency. Regression equation obtained is Y = 75,311 + 0.212 X, which means there is a positive influence between family social support to reciliency with the value F = 22.842, p = 0.000 < 0.05 (significant). The amount of influence (R Square) to the occurrence of family social support against reciliency is 0,297 which means that the family sosial support influence the reciliency by 29,7% and the remaining 70,3% influenced by other factors outside of family social support. It can be interpreted any significant positive effect of family sosial support and the reciliency. The study concluded that the higher score on family sosial support, have the higher also the reciliency of mother with mentally retrarded child and if a mother with mentally retarded child has a lower score on family sosial support it will also lower the reciliency. Key words: Mentally retarded, family social support, reciliency